2019
DOI: 10.1016/j.redox.2019.101194
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to adaptive homeostasis in an hyperoxia-induced model of accelerated ageing

Abstract: The Nrf2 signal transduction pathway plays a major role in adaptive responses to oxidative stress and in maintaining adaptive homeostasis, yet Nrf2 signaling undergoes a significant age-dependent decline that is still poorly understood. We used mouse embryonic fibroblasts (MEFs) cultured under hyperoxic conditions of 40% O 2 , as a model of accelerated ageing. Hyperoxia increased baseline levels of Nrf2 and multiple transcriptional targets (20S Proteasome, Immunoproteasome, Lon protease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…Thus, Bach1 plays an important role in the redox induction of HO-1 and NQO1 [ 157 , 161 ]. Recently, Pomatto and colleagues demonstrated in vitro that hyperoxia strongly elevates Bach1 levels and the competitive effect of Bach1 and Nrf2 increases in a time-dependent manner [ 162 ]. Additionally, silencing Bach1 increases basal expression of Nrf2-regulated antioxidant genes in both the young and older human bronchial epithelial cells [ 163 ], suggesting that Bach1 is a potential target for antiaging intervention.…”
Section: Bach1 and C - Mycmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Bach1 plays an important role in the redox induction of HO-1 and NQO1 [ 157 , 161 ]. Recently, Pomatto and colleagues demonstrated in vitro that hyperoxia strongly elevates Bach1 levels and the competitive effect of Bach1 and Nrf2 increases in a time-dependent manner [ 162 ]. Additionally, silencing Bach1 increases basal expression of Nrf2-regulated antioxidant genes in both the young and older human bronchial epithelial cells [ 163 ], suggesting that Bach1 is a potential target for antiaging intervention.…”
Section: Bach1 and C - Mycmentioning
confidence: 99%
“…Davies and Forman have proposed that although Bach1 and c - Myc expression increased with age, continual adaptive homeostasis contributes to lower cancer risk [ 171 ]. Additionally, Pomatto et al believe that changes in the balance of Nrf2 , Bach1 , and c - Myc levels may be the cause of serious disturbances to the stress response and adaptive homeostasis during chronic hyperoxia and aging [ 162 ]. Nevertheless, research has mainly focused on quantitative changes when examining the interaction between the two inhibitors, Nrf2, and aging.…”
Section: Bach1 and C - Mycmentioning
confidence: 99%
“…infection since the action of ROS is nonspecific and causes damage to the surrounding host cells, consequently leading to inflammation and tissue injury (Morgado et al, 2018;Herb and Schramm, 2021). Therefore, in the presence of pro-oxidant molecules, such as • O − 2 , adaptive homeostasis mechanisms must be activated as a way to protect against tissue damage (Pomatto et al, 2019). Despite producing • O − 2 in a more pronounced manner, mice of the C57BL/6 strain showed higher collagen deposition, suggesting an ability to balance pro-and antioxidant properties, thus explaining the concomitant elimination of the parasite combined with the tissue protection capacity found in C57BL/6 mice (Morgado et al, 2018).…”
Section: The Macrophages Recruited To the Lesion Site Are Important For The Evolution Of Edema And In The Arginase-1 Presencementioning
confidence: 99%
“…(H) Chromatin immunoprecipitation (ChIP)-polymerase chain reaction (qPCR) analysis validates the enrichment of BACH1 at the enhancer of CDKN1A gene (n 3 independent experiments, data are mean ± SEM, unpaired 2-tailed t-test, *p < 0.05). (Pomatto et al, 2019). Our recent study showed that BACH1 recruited an essential pluripotency regulator NANOG and the MLL/SET1 complexes to maintain the activity of promoters and (super-) enhancers in embryonic stem cells (Niu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%